Regular short haemodialysis in end-stage renal failure. Issue 5986 (27th September 1975) - Martin, A M; Oduro-Dominah, A; Gibbins, J K; Devapal, D; Mitchell, D C
Abstract : A study was made of thrice weekly haemodialysis of 3-3 1/2 hours' duration using a large surface area dialyser in patients with end-stage renal failure. Body water, potassium, and blood pressure control were satisfactory and comparable with the more widely used long dialysis schedules (6-9 hours thrice weekly). Patient rehabilitation was improved overall and the regimen enabled the dialysis unit to treat more patients despite a reduction in technical and nursing staff. The technique proved inadequate, however, in two patients with an intercurrent infection, and more intensive dialysis in recommended in such cases.